Exploring the Effects of Full-Day Kindergarten on School Absenteeism for Children With Disabilities: Evidence From State Policy Mandates in the United States. (April 2022) - Gottfried, Michael A.; Jacob Kirksey, J.
Student absenteeism is a barrier to learning and an issue that requires policy intervention. Students with disabilities are of particular concern, as they miss school more often than students in any other demographic group. Affecting a key attribute of school structures, policies promoting full-day kindergarten began as an effort to improve opportunities for students from disadvantaged backgrounds, but no studies have provided causal evidence as to whether full-day kindergarten enrollment relates to school attendance. No studies have examined whether effects exist for students with disabilities in the long term. Using a nationally representative sample of children with disabilities in the United States ( N  = 2, 120), we employed an instrumental-variable strategy that capitalized on state-level policy shifts of full-day kindergarten offerings as an exogenous source of variation. We found that full-day kindergarten structures related to a sharp increase in absenteeism for children with disabilities in kindergarten and first and second grades. We found no relationship to absenteeism for these children in later years of primary schooling. We discuss policy implications of these findings.